Effect and comparison of cognitive self-compassion and mindfulness on educational well-being of overweight students - Reza Nazeri; Hossein Lotfabadi; Hossein Pourshahriar (Gonabad University of Medical Sciences, 2019)
Overweight and obesity are common issues that have increased in children and adolescents in recent years. Along the physical problems, the psychological state of these individuals has also been considered by researchers. The purpose of the present study was to investigate the effect of cognitive self-compassion and mindfulness on the educational well-being of overweight adolescent students. The research method was a pretest-posttest with a control group. The participants consisted of 60 male overweight students (each group, 20) who were selected through a purposeful sampling and were assigned to two experimental and one control groups. Two questionnaires including educational engagement scale and the pleasure of physical activity scale were used to collect data. One group received cognitive self-compassion and the other group received mindfulness training and the control group did not receive any training. According to the results that self-compassion training and mindfulness significantly increased academic engagement and enjoyment of physical activity. The findings showed that there was no difference between the two methods of increasing the pleasure of physical activity, but mindfulness training had a greater effect on increasing academic engagement. Overall, the results showed that these two methods could significantly increase the educational well-being of overweight students.